Virulence-genes Rib and Bca in Serotypes of Group B Streptococcus (GBS) Isolated from Symptomatic Pregnant Women in East Coast Malaysia - Bahez, Ayesha; Mustafa Mahmud, Mohammed Imad Al-Deen; Hamzah, Hairul Aini; Wahid, Hanan Hamimi (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Group B streptococcus (GBS) is a leading cause of maternally-acquired invasive infections in neonates. Nowadays maternal immunization is of utmost demand for prevention of these infections. We undertook capsular serotyping and virulence factor genes identification for local GBS isolates as a pilot study, to identify potential candidates to propagate vaccine development. MATERIALS AND METHODS: This is a descriptive lab -based study to determine GBS serotypes and presence of genes coding virulence factors bca and rib in isolates obtained from symptomatic pregnant women in Hospital Tengku Ampuan Afzan, Kuantan, Pahang, Malaysia. Sixty-two GBS isolates from high vaginal swabs were collected. Latex agglutination test was performed to determine GBS serotypes. Real-time PCR was done to determine the presence of virulence genes. RESULTS: Of the 62 GBS isolates, 77.4% were serologically typeable, and 22.6% were non -typeable. Serotypes Ia and Ib (16.1% each) were the most common capsular types, followed by II, V, and VII (9.7% each), III (8.1%), VI (6.5%), and VIII (1.6 %). Furthermore, 67.7% of the isolates harboured the rib gene while 98.4% possessed the bca gene. CONCLUSION: The five known prevalent serotypes worldwide, do not match the CPS distribution in symptomatic pregnant women in Kuantan. However, the frequency of virulence genes rib and bca is high among our isolates, which if confirmed by further bigger and wider studies makes the proteinaceous vaccine, N-terminal domains of Rib and AlpC a suitable candidate for GBS prevention in this geographical area.